PULMONARY EMBOLISM IN THE PRACTICE OF AN OBSTETRICIAN-GYNECOLOGIST (CLINICAL CASE) - Елена Владимировна Рудаева; Юлия Валерьевна Васютинская; Любовь Борисовна Николаева; Светлана Ивановна Елгина; Кира Борисовна Мозес (Мать и дитя в Кузбассе)
Pulmonary embolism (PE) is a potentially life-threatening condition that can occur during pregnancy and poses a significant risk to both mother and fetus. It is a major cause of pregnancy-related morbidity and mortality in any trimester. The incidence of PE during pregnancy is estimated to be approximately 1 in 1000 pregnancies. The mortality rate among pregnant women with PE is approximately 3 %, which is significantly higher than among non-pregnant women with PE.